Effect of aqueous extract of Rheum ribes on cisplatin-induced nephrotoxicity in rat - Mousa-; Ziba Rajaei; Zakieh Keshavarzi; Mohsen Ghasem Shirazi; Vahedeh Toosi (Wolters Kluwer Medknow Publications, 2013)
Objective: The purpose of the present study was to examine whether Rheum ribes extract prevents cisplatin-induced nephrotoxicity. Materials and Methods: The animals were divided into three groups: Group A considered as control group, group B were treated with cisplatin (3 mg/kg B.W. for 3 alternative days), and group C further to cisplatin received the aqueous extract of Rheum ribes (150 mg/rat). Results: Blood urea nitrogen (BUN) level increased in group B on days 14 and 42 compared to day 0 ( P < 0.001); it was also increased in group B vs. group A on day 14 ( P < 0.001). Rheum ribes extract decreased the serum BUN level on day 14 compared to group B ( P < 0.001). Serum creatinine level in group B had a similar profile as serum BUN level but Rheum ribes had no effect on blood creatinine level. Serum cholesterol level was increased in group B on days 14 and 42 compared to day 0 ( P < 0.001). Also, cholesterol level was significantly increased in group B when compared to group A on day 14 ( P < 0.001). Rheum ribes decreased the blood cholesterol level on day 42 in comparison to group B ( P < 0.001). Serum glucose level was increased in group B on days 14 and 42 vs. day 0 ( P < 0.001). Also, glucose level was significantly increased in group B when compared to group A on day 42 ( P < 0.001). Rheum ribes increased the serum glucose level on days 14 and 42 compared to day 0 ( P < 0.05). Histology of kidneys exposed to cisplatin showed renal injury, but Rheum ribes had no effect on the kidney architecture. Conclusion: Cisplatin-induced nephrotoxicity was confirmed in our study. Although Rheum ribes had some effects on biochemical parameters; its effect on renal histology in injured kidney was insignificant.